Analisis Proses Kerja Staff Aviation Security (AVSEC) Dalam Penanganan Bagasi untuk Menunjangan Keamanan dan Keselamatan Penerbangan di Bandar Udara Tjilik Riwut Palangkaraya - Yunika, Fera; Astutik, Septiyani Putri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Aviation Security is aviation security personnel who already have a license who are assigned the task of inspecting passengers and passenger luggage to support flight security and safety. In carrying out the duties and responsibilities of Aviation Security personnel, work processes must be in accordance with Standard Operating Procedures (SOP). The purpose of this research is to find out the Aviation Security work process, what obstacles Aviation Security personnel experience, and how Aviation Security personnel handle problems with passengers and passenger luggage at Tjilik Riwut Palangkaraya Airport. This research is a qualitative type research, the data collection methods in this research are interviews, documentation, observation, library research, and research that takes place at Tjilik Riwut Palangkaraya Airport from 1 October to 30 November 2022. The results of this study are that all Aviation Security work processes at Tjilik Riwut Palangkaraya Airport in accordance with their rank have been carried out properly in accordance with the Standard Operating Procedures (SOP), but there are still several inhibiting factors including the X-ray machine, the monitor screen has an error, and the shortage of Aviation Security personnel, which has become an obstacle to checking passengers and their luggage. Keywords: aviation security work process, standard operating procedures, airport.